2012
DOI: 10.1007/s10531-012-0371-6
|View full text |Cite
|
Sign up to set email alerts
|

Diaspores and phyto-remains accidentally transported to the Antarctic Station during three expeditions

Abstract: The aim of the project was to assess the size and species range of alien plant diaspores and phyto-remains transported into the Polish Antarctic Station during three Antarctic expeditions. Our study clearly demonstrates that many diaspores can be quite easily unintentionally transported in good conditions to the Antarctic. In the analyzed material there were present diaspores of invasive species. All identified species belong to 20 families. The most abundant were Asteraceae and Poaceae species. The most inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
(49 reference statements)
2
34
0
Order By: Relevance
“…Also human dependent seed transport may play a role in the species spread, similarly to the way in which seeds get transported to Antarctic research stations (see e.g. Lee and Chown 2009;Lityńska-Zając et al 2012).…”
Section: Soil Seed Bank Size In Antarctic Conditionsmentioning
confidence: 99%
“…Also human dependent seed transport may play a role in the species spread, similarly to the way in which seeds get transported to Antarctic research stations (see e.g. Lee and Chown 2009;Lityńska-Zając et al 2012).…”
Section: Soil Seed Bank Size In Antarctic Conditionsmentioning
confidence: 99%
“…Their manuscript submission was received by the editorial staff on January 5, 2015 and published online on March 10, 2015 (Hughes et al 2015) we were working on the initial steps of eradication just as snow cover retreated in February and March 2015 (see report: Eradication of a nonnative grass P. annua L. from ASPA No 128 Western Shore of Admiralty Bay, King George Island, South Shetland Islands 2015). All of our earlier research regarding the biology and genetics of P. annua at Arctowski (Olech and Chwedorzewska 2011;Lityńska-Zając et al 2012;Wódkie-wicz et al 2013Wódkie-wicz et al , 2014Molina-Montenegro et al 2014;Pastorczyk et al 2014;Chwedorzewska et al 2015;Galera et al 2015;Giełwanowska et al 2015; was aimed at informed eradication/control of the species. Our actions preceded by the stated initial research enabled an analysis of the invasion process in the Antarctic and provided detailed documentation of eradication.…”
Section: Discussionmentioning
confidence: 99%
“…The project was preceded by detailed necessary research investigating the biology of the species in accordance to guidelines regarding the eradication/control of alien species by Simberloff (2003a, b). The distribution, morphology, ecology, genetics, physiology, expansion history and potential sources of introduction of the species was determined through multi-author interdisciplinary studies (e.g., see Olech and Chwedorzewska 2011;Lityńska-Zając et al 2012;MolinaMontenegro et al 2014;Pastorczyk et al 2014;Chwedorzewska et al 2015;Giełwanowska and Kellmann-Sopyła 2015;Giełwanowska et al 2015;. The research showed that the species is expanding in the anthropogenic sites as well as starts to invade native communities (Olech and Chwedorzewska 2011), has a distinctive morphological architecture in response to local harsh conditions and produces a viable soil seed bank (Wódkiewicz et al 2013(Wódkiewicz et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excellent vector for the transfer of fungal and other propagules to and within Antarctic regions is via humans and associated cargo, including food (Whinam et al 2005;Chwedorzewska 2009;Hughes et al 2011;Lityńska−Zając et al 2012;Chwedorzewska et al 2013). Hughes et al (2011) identified 19 spe− cies of fungi on rotting fruit and vegetables, also on the packaging and associated soil, most of which have previously been reported in different regions of the Ant− arctic.…”
Section: Introductionmentioning
confidence: 99%